Effects of sexual assault and sexual harassment on separation from the U.S. military findings from the 2014 RAND military workplace study - Morral, Andrew R.; Matthews, Miriam; Cefalu, Matthew; Schell, Terry L.; Cottrell, Linda (Rand Corporation, 2021)
Sexual assault and sexual harassment have a variety of consequences harmful to those who are targeted, including psychological and physical health effects. In addition, sexual assault and harassment may have deleterious and costly consequences for employers if the abuse results in higher turnover or low morale and productivity. This report describes data analyses designed to assess the effects of sexual assault and sexual harassment on service members' decisions to separate from the military. The researchers found that exposure to sexual assault (as determined by survey responses) doubled the odds that a member would separate from the military in the ensuing 28 months. Over this period, an estimated 2,000 more separations occurred than would be expected had members not been sexually assaulted, and 8,000 separations (or roughly 8 percent of all separations) were similarly associated with sexual harassment. Secondary analyses demonstrated that separations associated with sexual assault and harassment were disproportionately voluntary — that is, the service members were not discharged for problem behaviors or other failures to adhere to standards or expectations in the military. These findings suggest that sexual assault and harassment are costly for both the affected service members and the services and that they harm military readiness. The report concludes with recommendations for how the Department of Defense could use this study's findings to reduce sexual assault, sexual harassment, and the separations associated with these experiences
Keywords: Sexual harassment in the military / United States; Rape in the military / United States; Employee retention / United States; United States / Armed Forces / Personnel management